Decentralization of intertemporal economies with discounted maximin criterion. - Kaganovich, Michael (International Economic Review, 2000)
The intertemporal decentralization literature scrutinizes the ability of markets to achieve dynamically optimal allocation of resources. Put differently, it examines the possibility of designing a mechanism enabling short-lived agents to make independent decisions compatible with long-run optimum. The Hurwicz and Weinberger impossibility result states that the mechanisms that are both privacy preserving and optimal fail to exist when an infinite-horizon optimum is defined by Ramsey-type criteria with discounting. However, for a special case where the economy cannot sustain growth and agents do not discount future utilities, it is known that a decentralized mechanism using rolling plans is in a certain sense asymptotically optimal. To address the problem of possibility of decentralization mechanisms in a sustainable growth economy with discounting, I consider a “discounted maximin” optimality criterion. It selects the programs that sustain growth at a given rate. The article argues that this criterion is consistent with the principles of intergenerational justice, which can be defined in terms of intergenerational Nash equilibrium. Furthermore, the article demonstrates that a decentralized mechanism designed on the basis of rolling plans generates decisions that are asymptotically optimal in terms of the discounted maximin. Reprinted by permission of the publisher.